2006
DOI: 10.1038/nature05115
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 expression on HIV-specific T cells is associated with T-cell exhaustion and disease progression

Abstract: Functional impairment of T cells is characteristic of many chronic mouse and human viral infections. The inhibitory receptor programmed death 1 (PD-1; also known as PDCD1), a negative regulator of activated T cells, is markedly upregulated on the surface of exhausted virus-specific CD8 T cells in mice. Blockade of this pathway using antibodies against the PD ligand 1 (PD-L1, also known as CD274) restores CD8 T-cell function and reduces viral load. To investigate the role of PD-1 in a chronic human viral infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

136
2,293
18
22

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 2,386 publications
(2,504 citation statements)
references
References 26 publications
136
2,293
18
22
Order By: Relevance
“…Several groups have recently reported that PD-1 expression on peripheral blood CD8 þ T cells is increased during HIV infection and regulate T-cell survival. [34][35][36] Herein, we also demonstrated that induction of PD-1 is increased in Mes LNs of non-controllers and expression of PD-1 is enhanced in vitro by TGF-b. Although, we speculate a role of PD-1 in Mes LNs favoring immunosupression, a formal proof that blockade of PD-1/PD-L1 interaction will restore T-cell function and prevent death remains to be addressed once adequate reagents are available.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Several groups have recently reported that PD-1 expression on peripheral blood CD8 þ T cells is increased during HIV infection and regulate T-cell survival. [34][35][36] Herein, we also demonstrated that induction of PD-1 is increased in Mes LNs of non-controllers and expression of PD-1 is enhanced in vitro by TGF-b. Although, we speculate a role of PD-1 in Mes LNs favoring immunosupression, a formal proof that blockade of PD-1/PD-L1 interaction will restore T-cell function and prevent death remains to be addressed once adequate reagents are available.…”
Section: Discussionsupporting
confidence: 57%
“…In HIV-infected individuals, it has been shown that blocking such interaction increases the capacity of peripheral blood HIV-specific CD8 þ T cells to proliferate and survive. [34][35][36] While TGF-b appears necessary to prime cells of SIV-infected macaques to undergo apoptosis, it is not sufficient in and by itself to fully induce the process, as we have been unable to induce death by simply adding TGF-b on T cells from healthy macaques, in spite of inducing PD-1 expression. This may however reflect the lack of PD-L1 expression in our in vitro culture system.…”
Section: Discussionmentioning
confidence: 83%
“…6,39,40 We made a similar observation when incubating total splenocytes isolated from wild-type (WT), but not PD-L1 knockout (KO) mice with anti-PD-L1 antibody (Figure 3a; compare lanes 1–2 and 3–4 in Figure 3b), thus demonstrating antibody specificity. However, co-culture of WT splenocytes with WT adipocytes significantly dampened the anti-PD-L1 antibody effect on CD8 + IFNγ + T cells (compare lanes 1–2 and 5–6 in Figure 3b).…”
Section: Resultsmentioning
confidence: 56%
“…These trends have been confirmed in human studies showing that elevated levels of B7-H1 (REF. 47) and PD1 (REFS 48,49) are associated with T-cell exhaustion and depletion in HIV, and T-cell function can be restored in vitro by using B7-H1-specific antibody to antagonize the co-inhibitory interaction between B7-H1 and PD1. The commonality between these and other earlier observations of the importance of co-inhibition mediated by B7-H1-PD1 interactions is that they involve chronic conditions.…”
Section: Anergymentioning
confidence: 99%